Evaluation of Conservative and Surgical Treatment in Patients with Mirizzi Syndrome - Gaibullayev Temurbek Zakirovich; M.M. Akbarov; M.S. Nishanov; Usmonov A.A (Peerian Journals Publishing, 2023)
Mirizzi syndrome is a rare and difficult to treat clinical condition. However, recent advances in technology have opened up new possibilities for surgeons to better diagnose and treat this condition. Laparoscopic cholecystectomy is the gold standard treatment for symptomatic gallstones. A gallstone that is outside the gallbladder or has formed in a neighboring organ, needs further treatment, may be difficult to treat safely or effectively with a laparoscopic approach.
Keywords: mirizzi syndrome; choledocholithiasis; cholecystocholedochal fistula